2011
DOI: 10.1037/a0021895
|View full text |Cite
|
Sign up to set email alerts
|

The relation between instrumental musical activity and cognitive aging.

Abstract: Objective Intensive repetitive musical practice can lead to bilateral cortical reorganization. However, whether musical sensorimotor and cognitive abilities transfer to nonmusical cognitive abilities that are maintained throughout the life span is unclear. In an attempt to identify modifiable lifestyle factors that may potentially enhance successful aging, we evaluated the association between musical instrumental participation and cognitive aging. Method Seventy older healthy adults (ages 60–83) varying in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
202
7
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(249 citation statements)
references
References 65 publications
25
202
7
15
Order By: Relevance
“…Similarly, these findings contrast with other work finding musician advantages in task switching (Hanna-Pladdy & MacKay, 2011;Moradzadeh et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similarly, these findings contrast with other work finding musician advantages in task switching (Hanna-Pladdy & MacKay, 2011;Moradzadeh et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…For example, music is most often played in coordination with others (Palmer, 2013), which requires switching between multiple auditory streams (Loehr, Kourtis, Vesper, Sebanz, & Knoblich, 2013) and adjusting to other performers (e.g., Loehr & Palmer, 2011;Moore & Chen, 2010). Thus music performance may be associated with relatively general switching advantages, and musicians have indeed been found to outperform non-musicians on switching tasks (Hanna-Pladdy & MacKay, 2011;Moradzadeh, Blumenthal, & Wiseheart, 2014; see also Bugos, Perlstein, McCrae, Brophy, & Bedenbaugh, 2007;Zuk, Benjamin, Kenyon, & Gaab, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this interpretation, individuals have been shown to exhibit increasingly faster RTs as they accumulate more musical practice hours (Jentzsch et al, 2014). Moreover, only adults with at least 10 years of musical practice display advantages on non-verbal memory, naming and executive functioning, compared to controls (Hanna-Pladdy & Mackay, 2011). However, this account restricts the generalizability of the present findings.…”
Section: Discussioncontrasting
confidence: 53%
“…As the ability to prepare movements slows with age (Stelmach et al, 1988;Seidler et al, 2010), musical practice could serve as a potential intervention to delay or prevent such aging-related decline (Hanna-Pladdy & MacKay, 2011; As mentioned earlier, musicians have been reported to show structural enlargements in motoric areas of the brain. Musicians may therefore be more efficient at preparing their actions compared to non-musicians (Jäncke et al, 2000).…”
mentioning
confidence: 99%
“…Of note, but not discussed in this review, is that cognitive control has also been shown to be significantly enhanced by physical exercise in adults (for reviews, see Kramer and Erickson 53 and Hillman et al 55 ) and children, 56 by musical training, [57][58][59] and by meditation-based approaches. [60][61][62] Perhaps in the future a combined approach utilizing both game-based training and these alternative training procedures may prove most useful for training older populations and children and adults with attention deficits and workforce training such as for military personnel and even surgeons, 63 as well as other application to various neurological and psychiatric disorders.…”
Section: Figmentioning
confidence: 99%